Variations in carbon stocks across traditional and improved agroforestry in reference to agroforestry and households’ characteristics in Southeastern Ethiopia - Boja Tilinti; Mesele Negash; Zebene Asfaw; Teshale Woldeamanuel (Heliyon)
Agroforestry systems help to mitigate climate change by storing carbon in biomass, soils and products. The potential of various homegarden agroforestry (HGAF) practices as a carbon sink in reference to HGAF and household characters has not been adequately studied. Therefore, this study empirically assessed the effects of HGAF practices, HGAF size, HGAF age, and household wealth status on carbon stock accumulation in southeastern Ethiopia. Perennial plant inventory data, litter and soil samples were collected from 96 HGAF farms (48 traditional and 48 improved), consisting of 200 sample plots with a plot size of 20 m × 20 m. A total of 288 soil samples were collected from depths of 0–30 cm and 30–60 cm to analyze the spatial and vertical distribution of carbon. The results indicated that biomass carbon in improved HGAF practice was about 11.8 % higher than in traditional ones. Old age HGAF had 8.7 % and 49.4 % significantly higher biomass carbon than medium and young age HGAF, respectively. Soil organic carbon varied significantly based on HGAF practices, HGAF size, HGAF age and household wealth status (p < 0.05). The mean ecosystem carbon stock of traditional HGAF was by 17.2 % higher than that of improved practices. Our results revealed that the potential carbon stocks of the HGAF ecosystem depend on the types of HGAF, household wealth and soil depth. Thus, HGAF should be managed as a viable land use option to help mitigate climate change, while also offering food and income opportunities for smallholder farmers in the studied region and beyond.